2016
DOI: 10.5194/amt-9-1701-2016
|View full text |Cite
|
Sign up to set email alerts
|

3-D water vapor field in the atmospheric boundary layer observed with scanning differential absorption lidar

Abstract: Abstract. High-resolution three-dimensional (3-D) water vapor data of the atmospheric boundary layer (ABL) are required to improve our understanding of land-atmosphere exchange processes. For this purpose, the scanning differential absorption lidar (DIAL) of the University of Hohenheim (UHOH) was developed as well as new analysis tools and visualization methods. The instrument determines 3-D fields of the atmospheric water vapor number density with a temporal resolution of a few seconds and a spatial resolutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 79 publications
(89 reference statements)
2
63
0
Order By: Relevance
“…Within the considered time interval, z i is found to be characterised by a limited variability, with a mean value z i of 1290 m a.g.l, and a standard deviation of 75 m. The minimum and maximum values of z i during the observation period are 1140 and 1440 m a.g.l., respectively. This result is in very good agreement with the simultaneous measurements performed by the University of Hohenheim Differential Absorption Lidar (UHOH-DIAL; Wagner et al, 2013;Späth et al, 2016), deployed in Hambach, approx. 4 km E-SE, with a mean value of 1295 m and a standard deviation of 86 m .…”
Section: Water Vapour Mixing Ratio Temperature and Backscatter Fieldssupporting
confidence: 88%
“…Within the considered time interval, z i is found to be characterised by a limited variability, with a mean value z i of 1290 m a.g.l, and a standard deviation of 75 m. The minimum and maximum values of z i during the observation period are 1140 and 1440 m a.g.l., respectively. This result is in very good agreement with the simultaneous measurements performed by the University of Hohenheim Differential Absorption Lidar (UHOH-DIAL; Wagner et al, 2013;Späth et al, 2016), deployed in Hambach, approx. 4 km E-SE, with a mean value of 1295 m and a standard deviation of 86 m .…”
Section: Water Vapour Mixing Ratio Temperature and Backscatter Fieldssupporting
confidence: 88%
“…Currently it is difficult to evaluate the quality of the vertical structures of temperature, moisture, and wind due to the unavailability of high spatial and temporal resolution atmospheric profiler data like differential absorption lidar and Raman lidar instrumentation (Hammann et al 2015;Späth et al 2016).…”
Section: Vertical Distribution Of Temperature and Moisturementioning
confidence: 99%
“…A temperature rotational Raman lidar (TRRL) measured temperature profiles Hammann et al, 2015;Radlach et al, 2008) and a water vapour DIAL measured absolute humidity profiles Späth et al, 2016;Wagner et al, 2013). In contrast to the Raman lidar technique, the DIAL technique, which is based on the alternating emission of laser pulses at frequencies strongly and weakly absorbed by water vapour, does not require calibration.…”
Section: Hambach Supersitementioning
confidence: 99%
“…Barrera-Verdejo et al (2016) similarly showed the positive impact of combining rotational Raman lidar measurements of BASIL with microwave radiometer observations for improving the temperature profile above the boundary layer. Based on scanning measurements with the water vapour DIAL of IPM made during HOPE-Jülich, Späth et al (2016) (see Sect. 2.1.1) presented a detailed study of the 3-D structure of the water vapour field between the supersites HAM, KRA, and JUE with a range resolution of 30-300 m and a temporal resolution in the range of 10 s for each profile.…”
Section: Thermodynamic Properties Of the Atmospherementioning
confidence: 99%